(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Panchamrut is a holy and sacred traditional ayurvedic drink that is made up of five ingredients (milk, curd, ghee, honey, sugar). It is used for the spiritual purpose like offering to God during poojas and for religious purpose like used in Hindu rituals for the Abhishekam of God sculptures by devotees. Not only spiritual and religious aspects, it also has healthier aspects. The Panchamrut word is a mixture of two Sanskrit words i.e. Panch and Amrut. Panch means five and Amruta means nectar of gods. As per Ayurveda, when these five ingredients are mixed together in equal proportions is called as Divya Panchamrut. Divya means divine and auspicious. All these five Dravyas have their medicinal importance and mentioned in almost every ayurvedic texts but very few authors talked about Panchamrut individually. Everyone has aware of its religious and spiritual benefits but it has numerous health benefits also like it improves immunity, acts as Rasayana, enhances brain function and memory. It has anti-ageing properties and many more. This article will help you to know about the healthier aspects of Panchamrut with immense benefits.